Bone safety of dual-release hydrocortisone in patients with autoimmune primary adrenal insufficiency - Bioletto, Fabio; Barale, Marco; Parasiliti-Caprino, Mirko; Giannelli, Jacopo; Campioni, Lorenzo; Cappiello, Vincenzo; Di Carlo, Maria Chiara; Ghigo, Ezio; Procopio, Massimo; Giordano, Roberta (Frontiers in Endocrinology, 2023)
Background. Conventional glucocorticoids (C-GC) replacement regimens have a detrimental effect on skeletal health in patients with adrenal insufficiency (AI), ultimately leading to an increased fracture risk.The novel dual-release hydrocortisone (DR-HC) formulations are characterized by a more favourable safety profile on various clinical endpoints. Data comparing the impact of C-GC and DR-HC on bone, however, are scarce.Methods. Twenty-seven patients with autoimmune primary AI (PAI; 13 treated with C-GC and 14 treated with DR-HC) were evaluated to compare bone-related parameters between the two treatment groups.Results. No significant differences between the two treatments groups were observed with respect to bone turnover markers. Patients treated with C-GC showed a lower bone mineral density (BMD) at lumbar spine (LS; 0.791±0.195 vs 0.942±0.124 g/cm 2 , p=0.025) and at femoral neck (FN; 0.633±0.114 vs 0.716±0.088 g/cm 2 , p=0.045). Moreover, they were characterized by a lower trabecular bone score (TBS; 1.236±0.035 vs 1.383±0.030, p=0.004) and by a higher mean number of vertebral fractures per patient (0.75 vs 0 fractures, p=0.002). TBS was the best predictor of fracture risk, with a pseudo-R 2 of 0.593; moreover, at mediation analysis, it was able to fully explain the observed detrimental effect of C-GC, compared to DR-HC, on fracture risk.Conclusions. These results suggest that DR-HC is associated with less bone-related complications compared to C-GC in patients with PAI. Moreover, TBS seems to play a pivotal role in the mediation of the relationship between glucocorticoid treatment regimens and fracture risk.